Malaysia Day spirit - Abd Razak, Dzulkifli (2010)
MENTION the word "dove" and immediately a picture of a white-feathered bird symbolising peace and harmony comes to mind. Often, doves are released into the air to bring home this message worldwide. The most recent was during the 65th anniversary of the atomic bombings of Hiroshima and Nagasaki in Japan last month.